Multivisceral transplantation: a multifactorial approach (Research, Society and Development, 2022)
Multivisceral transplantation is the only way to restore nutrition through the digestive tract of patients who suffer from intestinal failure or who have inadequate absorption of macro and micronutrients. Most of these transplants occur in the pediatric population, mainly caused by short bowel syndrome, which disables the child's intestines to secrete fluid and absorb nutrition and energy efficiently. The reality of Brazilian patients who have this injury is very harsh, as the Unified Health System (SUS) and the private network do not offer multivisceral transplantation due to the lack of professionals who master the technique of this procedure. The study made use of scientific publications dated between 2015 and 2021 present in the SciElo, PubMed, Up To Date, Medical News Today, Google Scholar, New England Journal of Medicine and ABTO (Brazilian Association of Organ Transplantation) databases in Portuguese. and English addressing the topic “Multivisceral Transplantation”. Research projects, books, case reports and editorials were excluded from this review. From the analysis of the literature found, it was found that although rejection is still quite frequent, several advances have allowed the clinical application of multivisceral transplantation, such as the emergence of new immunosuppressive drugs, inducers, monoclonal and antilymphocytic antibodies. It is therefore concluded that, initially, this type of transplant did not present satisfactory results, but with the improvement of surgical techniques and infection control, the multivisceral transplant appears to be quite promising.